IntegrationReviewSolns

# IntegrationReviewSolns - Integration Review MATH 213-C...

This preview shows pages 1–5. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Integration Review MATH 213-C September 25, 2009 Evaluate the integrals. 1. Z 1 a 2 + x 2 dx,a 6 = 0 Solution: The integrand almost looks like the derivative of tan- 1 ( x ). Factor an a 2 out of the denominator: Z 1 a 2 + x 2 dx = 1 a 2 Z 1 1 + ( x a ) 2 dx Let u = x a ⇒ du = 1 a dx Thus Z 1 a 2 + x 2 dx = 1 a Z 1 1 + u 2 du = 1 a tan- 1 x a + c 2. Z 1 √- 5 + 6 x- x 2 dx Solution: Complete the square:- x 2 + 6 x- 5 =- ( x 2 + 6 x + 9) + 4 =- ( x- 3) 2 + 4 1 so Z 1 √- 5 + 6 x- x 2 dx = Z 1 p- ( x- 3) 2 + 4 dx = 1 2 Z 1 q 1- ( x- 3 2 ) 2 dx, for x- 3 2 < 1 Let u = x- 3 2 ⇒ du = 1 2 dx so that Z 1 √- 5 + 6 x- x 2 dx = Z 1 √ 1- u 2 du = sin- 1 x- 3 2 + c, for x- 3 2 ≤ 1 3. Z 4 x + 1 2 x 2 + 4 x + 10 dx Solution: This one requires a bit of thought. Note that the derivative of the denominator is 4 x + 4, which is almost the same as the numerator. Thus we add and subtract 3 from the numerator: Z 4 x + 1 2 x 2 + 4 x + 10 dx = Z 4 x + 4 2 x 2 + 4 x + 10 dx- Z 3 2 x 2 + 4 x + 10 dx For the first integral: let u = 2 x 2 + 4 x + 10 ⇒ du = 4 x + 4 and we have Z 4 x + 4 2 x 2 + 4 x + 10 dx = Z du u = ln 2 x 2 + 4 x + 10 . For the second integral, complete the square in the denominator: 2 x 2 + 4 x + 10 = 2( x 2 + 2 x + 1) + 10- 2 = 2( x + 1) 2 + 8 Page 2 and so- Z 3 2 x 2 + 4 x + 10 dx =- 3 Z 1 2( x + 1) 2 + 8 dx =- 3 8 Z 1 ( x +1 2 ) 2 + 1 dx Now let u = x + 1 2 ⇒ du = 1 2 dx and we find that- 3 8 Z 1 ( x +1 2 ) 2 + 1 dx =- 3 4 Z du u 2 + 1 =- 3 4 tan- 1 x + 1 2 . Putting it all together, Z 4 x + 1 2 x 2 + 4 x + 10 dx = ln 2 x 2 + 4 x + 10- 3 4 tan- 1 x + 1 2 + c. (This is an indefinite integral, so we must remember to include the constant of integration, c .) 4. Z ( x 2- 5) 2 dx Solution: Expand the integrand: Z ( x 2- 5) 2 dx = Z ( x 4- 10 x 2 + 25) dx = 1 5 x 5- 10 3 x 3 + 25 x + c. 5. Z 1 e x √ 1- e 2 x dx Page 3 Solution: Let u = e x ⇒ du = e x dx Thus Z 1 e x √ 1- e 2 x dx = Z e 1 du √ 1- u 2 = sin- 1 ( e )- sin- 1 (1) = sin- 1 ( e )- π 2 ....
View Full Document

{[ snackBarMessage ]}

### Page1 / 13

IntegrationReviewSolns - Integration Review MATH 213-C...

This preview shows document pages 1 - 5. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online